PENENTUAN LOKASI TERBAIK LINGKUNGAN PERUMAHAN DI PERKOTAAN DENGAN PENDEKATAN FUZZY - Siti Sulistiani; Oni Soesanto; Mohammad Mahfuzh Shiddiq (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2014)
Fuzzy logic provides a solution to the problem of uncertainty, because in real life often encountered things that are uncertain or vague and sometimes difficult to resolve firmly. Fuzzy logic is able to overcome the uncertainty in real-life cases. One is the problem of determining the right location to create a particular facility such as a residential neighborhood, where there are several factors to consider and sometimes difficult to decide firmly. To make a multi-criteria decision, there are several methods that can be used. But in this research that will be used is one method of Fuzzy Analytical Hierarchy Process (FAHP) is Method Extent Analysis Chang (1996). The purpose of this research is to determine optimal location of an urban housing environment by using Extent Analysis Chang Method. The decision-making process is carried out with the steps contained in Ext's Analysis (1996) method sequentially starting from criteria, sub criteria and alternatives. The final decision is made by ranking the normalized vector weighting of all criteria and sub criteria. Location A was chosen as the optimal location, because it has the highest ranking weighting that is 0.330.